Slovarji serije COBUILD in formalizacija definicijskega jezika - Krek, Simon (Jezik in slovstvo, 2004)
A decade and a half ago, English monolingual dictionaries from the COBUILD series initiated a mini-revolution in (English) monolingual lexicography. A few years ago, a series of bilingual dictionaries called the COBUILD BRIDGE dictionaries have emerged, which included the English-Slovenian Bridge Dictionary. The article presents the theoretical concept behind the COBUILD series with its specific corpus origins and whole-sentence definition style, as well as its trnasfer into a bilingual environment.
Keywords: angleščina; English; Slovene; slovenščina; slovarji; enojezični slovarji; dvojezični slovarji; COBUILD BRIDGE